Huldrich Zwingli se Von dem Touff, vom Widertouff und vom Kindertouff : Enkele aspekte van Zwingli se teologiese denke - Smith, D. J. (Hervormde teologiese studies, 1985)
Huldrich Zwingli's 'Von dem Touff, vom Widertouff und vom Kindertouff': Some aspects of Zwringli's theological thought The aim of this article is to let Zwingli speak for himself as he expresses himself in his treatise on baptism: Von dem Touff, vom Widertouff und vom Kindertouff. The use of secondary literature is avoided in an attempt to steer clear of an interpretation of Zvkfingli, predetermined by views formed by traditional conceptions handed down and tainted by dogmatic considerations. Zwingli's views on the following themes are discussed and certain conclusions are drawn: Zwingli as pioneer in the founding of infant baptism in both the New Testament as well as the covenant in the Old Testament; Zwingli's distinction of a fourfold usage and meaning of the word baptism; Zwingli and baptism as sign of obligation; Zwingli and the institution of baptism; Zwingli's usage of Scripture; Zwingli and the Holy Ghost.